Comparing the effects of Triptorelin and Calendula officinalis on size and pathology of induced endometriosis in rats. Issue 3 (September 2019) - Poordast, Tahere; Najib, Fatemeh Sadat; Tanide, Nader; Kanani, Afsoon; Mokhtari, Maral; Chaman-Ara, Kefayat
Background: Endometriosis is defined as the growth of endometrial glands and stoma extra-uterine sites. It is an estrogen-dependent inflammatory disease estimated to affect 10% of women of reproductive age. This study aimed at comparing the effects of Triptorelin and Calendula officinalis on the induced endometriosis in female rats. Materials and Methods: In this experimental study in an animal model, 52 rats with induced endometriosis were divided into four groups. The control group was treated with 0.5 mL/kg normal saline orally, the second group with single intramuscular injection of Triptorelin S.R.11.25 (3 mg/kg), the third group with Calendula 1000 mg/kg, and the fourth group with Calendula 2000 mg/kg for 6 weeks. The mean area and volume of endometriosis and pathological scores of endometriotic implants were compared between groups. Results: After 6 weeks of treatment, Triptorelin was able to reduce the mean area and volume of endometriotic implants (p < 0.05), but Calendula did not have a significant effect compared to the control group. Mean rank of pathologic score in Triptorelin group had a significant difference with the control group and Calendula 1000 mg/kg (adjusted α < 0.001, adjusted α = 0.004). There was no significant difference in score between the control group and Calendula 1000 mg/kg and 2000 mg/kg. Conclusion: Based on our findings in the used doses, Calendula was not effective for the treatment of experimental endometriosis in rats.